The Influence of the Rupiah Exchange Rate, Interest Rates and Inflation on Stock Prices (Case Study of the Indonesian Manufacturing Company Listed on the IDX) - Purwanto, Muhammad Rosi; Sari, Herlinda Maya Kumala (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
This research aims to find out whether the Rupiah Exchange Rate, Interest Rates and Inflation have an influence on stock prices using a case study of a manufacturing company listed on the IDX. In this research, the method used is a quantitative method and the analysis in this research is Multiple Linear Regression using the selected model, namely the Random Effect Model. Data collection in the research used documentation studies using secondary data obtained from company annual reports on the IDX. The sample in this research was 20 samples taken using purposive sampling technique. then analyzed using Eviews 12 software. This research uses independent variables, namely the Rupiah Exchange Rate, Interest Rates and Inflation, then the dependent variable is Stock Prices. The results of this research show that share prices are significantly influenced by interest rates. While the Rupiah exchange rate and inflation do not affect stock prices, the aim of this research is to find out how far the rupiah exchange rate, interest rates and inflation affect stock prices. The results of this research show that the interest rate variable shows a positive and significant relationship to stock prices.